Desenvolvimento de sistema de cálculo de unidades monitoras para feixes de fótons de 10 MV em radioterapia - Santos, Emily Caroline Coelho dos [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
In this work was developed and applied a spreadsheet to calculate monitor units (MU) for cases of treatment with photons beam with energy of 10 MV. Was used Microsoft Excel®, which can be easily found in the operating system of computers in medical physics services. In the spreadsheet were used data on the linear accelerator Elekta model Precise belonging to the Clínica de Radioterapia Arakawa - Hospital Unimed Bauru. The values of the physical parameters not provided in the equipment commissioning test were obtained by interpolation. The mathematical formulas for automatic search of these and other factors used in the calculations of MU were developed according to routines available in Excel. To verify the validity of the spreadsheet developed, we analyzed 10 technical files of different treatments performed with photon beam of 10 MV. The 10 cases studied have 56 radiation fields. The technical files show the values calculated with the commercial computerized planning system XiO® , as well as those determined manually by medical physicists at the clinic. These two values and those calculated by the independent verification worksheet used in the Radiotherapy Sector of the Hospital das Clínicas da Faculdade de Medicina de Botucatu were compared with those calculated using the methodology developed in this study. For most of the clinical cases analyzed, the calculated values of MU have discrepancies within the limit allowed by literature (± 5%). The largest percentage deviations occur when comparing the values of MU calculated by XiO® with those calculated through the spreadsheet developed in this work. This is explained by the difference in processing and calculation algorithm used by XiO® . Overall, it was verified that the use of the spreadsheet developed in this work optimized the routine medical physics service of the clinic, streamlining the calculations and minimizing the occurrence of errors and uncertainties arising from the mistaken manipulation of the parameters obtained in the data tables of the photon beam of 10 MV.

Neste trabalho foi desenvolvida e aplicada uma planilha para cálculo de unidades monitoras (UM) para casos de tratamentos com feixe de fótons com energia de 10 MV. Foi utilizado o Microsoft Excel®, que pode ser facilmente encontrado no sistema operacional dos computadores nos serviços de física médica. Na planilha empregou-se dados referentes ao acelerador linear Elekta modelo Precise pertencente à Clínica de Radioterapia Arakawa – Hospital Unimed Bauru. Os valores dos parâmetros físicos não fornecidos no teste de comissionamento do equipamento foram obtidos por interpolação. As fórmulas matemáticas para busca automática destes e demais fatores utilizados nos cálculos de UM foram desenvolvidas conforme rotinas disponíveis no Excel. Para verificação da validade da planilha desenvolvida, foram analisadas 10 fichas técnicas de diferentes tratamentos realizados com feixe de fótons de 10 MV. Os 10 casos estudados apresentam um total de 56 campos de radiação. As fichas técnicas exibem os valores de UM calculados com o sistema de planejamento computadorizado comercial XiO® , e também os determinados manualmente pelos físicos médicos da clínica. Estes dois valores e os calculados pela planilha de verificação independente utilizada no Setor de Radioterapia do Hospital das Clínicas da Faculdade de Medicina de Botucatu foram comparados com os calculados usando a metodologia desenvolvida neste trabalho. Para a maioria dos casos clínicos analisados, os valores de UM calculados apresentam discrepâncias dentro do limite permitido pela literatura (± 5%). Os maiores desvios percentuais se dão quando se compara os valores de UM calculados pelo XiO® com aqueles calculados através da planilha desenvolvida neste trabalho. Isto é explicado pela diferença no processamento e de algoritmo de cálculo usado pelo XiO® . De forma geral, verificou-se que o uso da planilha desenvolvida neste trabalho otimizou a rotina do serviço de física médica da clínica, agilizando os cálculos e minimizando a ocorrência de erros e incertezas oriundos da manipulação equivocada dos parâmetros obtidos nas tabelas de dados dos feixes de fótons de 10 MV.
Keywords: Radiotherapy; Monitor unit; Radioterapia; Unidade Monitora